OP65 Duration of sleep at 3 years of age is associated with fat, lean and bone mass at 4 years of age: findings from the Southampton Women's Survey. (2nd September 2014) - Baird, J; Hill, C; Robinson, SM; Godfrey, KM; Harvey, N; Cooper, C; Inskip, HM
Abstract : Background: Short sleep duration in childhood is associated with raised body mass index (BMI) suggesting that strategies to improve sleep might decrease obesity. Evidence suggests the relationship is due to an effect of sleep on adiposity but few studies have explored the relationship of sleep with other components of body composition. This study examined the relationship of childhood sleep with fat, lean and bone mass. Methods: We examined the relationship of sleep duration at age 3 years with body composition at 4 years within the Southampton Women's Survey, a population-based cohort study of 12, 500 women aged 20–34 years. Women who became pregnant and their children (n = 3140) were followed up. Mothers reported the time their child went to sleep at night and woke in the morning at age 3 and the length of daytime naps. Total sleep, in hours and minutes, was derived from these data. Fat, lean and bone mass were derived from a dual X-ray absorptiometry (DXA) whole body scan at 4 years of age in a subset of children. The relationship of sleep and body composition was assessed in multiple regression analyses, adjusting for the influence of potential confounding factors; regression coefficients (β) are standard deviation changes in DXA measurements per hour of sleep. Results: Mean total sleep duration of 898 children (475 boys, 425 girls) who had a DXA scan was 11.5 h. Sleep duration had a significant inverse association with BMI such that children who slept for shorter periods at 3 years had higher BMI at 4 years. In analyses adjusted for confounding factors including maternal educational attainment, pre-pregnancy BMI, smoking during pregnancy, child's age, sex, height at DXA, age last breastfed, dietary quality at 3 years, TV watching and hours actively on the move, sleep duration was significantly inversely associated with BMI (β=-0.2366, 95% CI -0.3724, -0.1007) and fat mass (β=-0.1188, 95% CI -0.2288, -0.0089) but also with lean mass (β=-0.1287, 95% CI -0.2142, -0.0434) and volumetric bone mineral density (β=-0.0039, 95% CI -0.0075, -0.0004). Conclusion: Consistent with other research, shorter sleep was associated with greater BMI and fat mass. We also found, however, that shorter sleep duration was associated with greater lean and bone mass suggesting that the relationship between sleep and BMI is not determined by an effect on adiposity alone.